Implementasi Model Pembelajaran IPA dalam Meningkatkan Kemampuan Argumentasi Ilmiah Peserta Didik Jenjang Sekolah Menengah : Studi Kepustakaan - Syarful Annam (Action Research Journal, 2026)
Argumentation skills are one of the main objectives of science learning because students who study science must know scientific explanations of natural phenomena, use them to solve problems and be able to understand other findings they obtain. This study is a Systematic Literature Review (SLR) that aims to identify and analyze the most effective learning models to improve students' scientific argumentation skills in science learning. This study was assisted by the Publish or Perish application to search for relevant research articles in the Google Scholar database using the keywords "science learning models", "scientific argumentation skills", and "high school". The search for literature study articles obtained 40 articles that met the inclusion criteria and were relevant for review. The results of the literature study indicate that one of the most effective learning models in improving students' scientific argumentation skills in science is Argument Driven Inquiry. The application of this learning model provided the highest average score compared to other models, with a range of 78-85